Staffing and workflow of a maturing institutional repository - Madsen, Debora L.; Oleen, Jenny K. (My University, 2013)
Institutional repositories (IRs) have become established components of many academic libraries. As an IR matures it will face the challenge of how to scale up its operations to increase the amount and types of content archived. These challenges involve staffing, systems, workflows, and promotion. In the past eight years, Kansas State University’s IR (K-REx) has grown from a platform for student theses, dissertations, and reports to also include faculty works. The initial workforce of a single faculty member was expanded as a part of a library-wide reorganization, resulting in a cross-departmental team that is better able to accommodate the expansion of the IR. The resultant need to define staff responsibilities and develop resources to manage the workflows has led to the innovations described here, which may prove useful to the greater library community as other IRs mature.
Keywords: Institutional repositories; Workflow management system; K-REx